2019
DOI: 10.1093/mnras/stz1304
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave emission from 3D explosion models of core-collapse supernovae with low and normal explosion energies

Abstract: Understanding gravitational wave emission from core-collapse supernovae will be essential for their detection with current and future gravitational wave detectors. This requires a sample of waveforms from modern 3D supernova simulations reaching well into the explosion phase, where gravitational wave emission is expected to peak. However, recent waveforms from 3D simulations with multi-group neutrino transport do not reach far into the explosion phase, and some are still obtained from non-exploding models. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 80 publications
9
98
1
Order By: Relevance
“…ported for most non-rotating 3D models (Andresen et al 2017;Srivastava et al 2019;Powell & Müller 2019). Our non-rotating models are detectable to similar distances.…”
Section: Detection Prospectssupporting
confidence: 59%
See 2 more Smart Citations
“…ported for most non-rotating 3D models (Andresen et al 2017;Srivastava et al 2019;Powell & Müller 2019). Our non-rotating models are detectable to similar distances.…”
Section: Detection Prospectssupporting
confidence: 59%
“…It employs the xCFC approximation for the space-time metric (Cordero-Carrión et al 2009). We use the fast multigroup neutrino transport method described in , including the updates listed in Powell & Müller (2019). We use a spatial resolution of 550x128x256 and 21 energy groups.…”
Section: Simulation Methodology and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 19−M model (black line), the results of high and low resolution models are displayed as thicker and thinner lines, respectively, than the line denoting the standard resolution model. vious studies addressed PNS convection in 3D (Glas et al 2019b;Walk et al 2019a;Powell & Müller 2019), but they were limited to a few models. Moreover, those studies generally focused on the relation between PNS convection and the lepton-emission self-sustained asymmetry (LESA) phenomenon (Tamborra et al 2014;O'Connor & Couch 2018;Vartanyan et al 2019b)) or gravitational radiation (Powell & Müller 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have revealed that the candidate ingredients of GW emission from stellar core collapse include rapid progenitor rotation, prompt convection, neutrino-driven convection, proto-neutron star (PNS) convection, g/ f -mode oscillation of the PNS, the standing accretion shock instability, and non-axisymmetric rotational instabilities (see, Dimmelmeier et al 2007;Ott et al 2007;Müller et al 2013;Cerdá-Durán et al 2013;Kuroda et al 2016a;Andresen et al 2017;Yakunin et al 2017;O'Connor & Couch 2018;Pan et al 2018;Powell & Müller 2019;Andresen et al 2019;Radice et al 2019;Vartanyan et al 2019, for collective references therein).…”
Section: Introductionmentioning
confidence: 99%